HUBUNGAN MEAN ARTERIAL PRESSURE DENGAN KEJADIAN MUAL MUNTAH PASCA OPERASI PADA PASIEN POST ANESTESI SPINAL DI RUMAH SAKIT BHAYANGKARA - Nonok Karlina (LPPM ITEKES Mahardika, 2020)
Nausea and vomiting are the most common complications after surgery with anesthesia. The incidence of nausea and vomiting of all patients undergoing surgery occurs in 30% of patients to 70% in hospitalized patients that arise within the first 24 hours. Spinal anesthesia techniques have disadvantages such as bradycardia, apnea, inadequate breathing, nausea / nausea and vomiting, headache after lumbar puncture, high or total spinal block, hypotension. Hypotension is one of the causes of nausea and vomiting in spinal anesthesia.The purpose of this study was to determine the relationship of mean arterial pressure with postoperative nausea and vomiting in post spinal anesthesia patients.The method in this study uses the correlation description method with a cross-sectional approach. The study was conducted in Recovery Room of Bhayangkara Indramayu Hospital in June - July 2018. The study population was all postoperative spinal anesthesia patients in Recovery Room Bhayangkara Hospital with a sample of 30 people taken by simple random sampling technique. Data analysis using descriptive analysis and bivariate test using chi-square correlation test.The results showed that the mean arterial pressure of the respondents were mostly in the high category (53.3%), and most respondents experienced 63.3% postoperative nausea and vomiting events.Statistical test results showed p value = 0.003. This shows a relationship between mean arterial pressure and the incidence of postoperative nausea and vomiting in post-spinal anesthesia patients at Bahayangkara Hospital.This study recommends the importance of nurses monitoring the blood pressure of post spinal anesthesia patients to reduce patient mortality.